The Wilderness Novelty Seeking Scale. Issue 2 (October 2014) - Próchniak, Piotr
The purpose was to present the new scale of novelty seeking in the context of wilderness. A study of the psychometric properties of the Wilderness Novelty Seeking Scale was conducted, with an exploratory and a confirmatory factor analysis being carried out and the coefficients of the scale's reliability and stability over time being tested. The convergent validity of the WNSS scale was indicated by positive correlations with sensation seeking, openness to experience, and need for cognition. The divergent validity of the WNSS scale was indicated by non-significant correlations with state-trait anxiety and depression. The correlation between the Wilderness Novelty Seeking Scale and psychological well-being was analyzed. The Wilderness Novelty Seeking Scale seems to be a reliable and valid tool.